Perkawinan Sesama Jenis Perspektif Hukum Indonesia dan Hukum Thailand - Difa Fibra Aisyah; Muhammad Teguh Syuhada (Jurnal Hukum Lex Generalis, 2023)
This research aims to discuss comparative laws regarding same-sex marriage in Indonesia and Thailand, with a focus on legal policy, social implications, and impact on generations. This research uses normative legal methods using secondary data sources originating from library materials and legislation. The research results show that Thailand, which is a country that tends to be progressive in recognizing LGBT rights, has initiated legislative steps that provide legal protection for same-sex couples, including the "Civil Partnership" Bill. In contrast, Indonesia, with a more conservative legal and cultural background, does not yet have a legal framework that supports the recognition of same-sex marriages. This research examines the legal frameworks of both countries, legislative challenges, and the social implications of same-sex marriage. This study seeks to provide policy recommendations based on a comparison of the two legal systems.